Calidad de vida y riesgo suicida en adolescentes - Ayllis Dalila, Guerrero Calero (2021)
ABSTRACT Adolescence represents a stage of transition to adulthood where the lifestyle that the subject leads will be an important factor in presenting suicidal behaviors. The present research is aimed to analyze the problematic quality of life and suicide risk in adolescents. This project is of a bibliographic review type with a quantitative-qualitative approach. The population was made up of 30 documents published between 2016 and 2021 in databases such as: Scopus, Scielo, Dialnet, MDPI, Google Scholar. Based on criteria, a sample of 20 scientific articles was determined, of which a methodological quality analysis was carried out using the Critical Review Form Quantitative Studies and Critical Review Form Qualitative Studies instrument authored by (Law et., Al 1998). In the research found, it is synthesized that adolescents perceive a better quality of life if they present domains in physical activity, psychological well-being, social acceptance, good relationship with parents, on the contrary, factors responsible for suicidal risk such as hopelessness, low self-esteem, stressful events, conflicts family, negative mood, impulsiveness. It was concluded that quality of life does not only refer to physical well- being but rather that it is integral in adolescents, where there will be essential determinants for good development among them: lifestyles, environment, social aspects, in turn being able to be related to risk factors such as: family dysfunction, mental health, inadequate parenting patterns, poverty, which could become suicide guides. Keywords: quality of life, suicidal ideation, suicide, adolescent, mental health. Reviewed by: Danilo Yèpez Oviedo English professor UNACH 0601574692